Carta de Carlos M. de Castro a Roberto H. Todd - Todd, Roberto H.; Castro, Carlos M. de (My University, 1924)
Carta relacionada a manifestación en San Juan.
Keywords: Partido Republicano (Puerto Rico); Republican party. Puerto Rico.